Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

First off, please excuse my n00bishness I have only just begun learning about algebraic manipulation of limits so this is probably a really dumb or obvious question.

I'm trying to solve the following limit:

$$ \lim_{x\to\pi/6}\frac{1 - 2\sin{x}}{2\sqrt{3}\cos{x} - 3} $$ This limit is $0/0$ if evaluated directly, so I tried multiplying by the conjugate of the denominator:

$$ \begin{align} & = \lim_{x\to\pi/6}\frac{(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3)}{(2\sqrt{3}\cos{x} - 3)(2\sqrt{3}\cos{x} + 3)}\\ & = \lim_{x\to\pi/6}\frac{(2\sin{x} - 1)(2\sqrt{3}\cos{x} - 3)}{(2\sqrt{3}\cos{x} - 3)(2\sqrt{3}\cos{3} + 3)} \\ & = \lim_{x\to\pi/6}\frac{2\sin{x} - 1}{2\sqrt{3}\cos{x} + 3}\\ & = \frac{2(1/2) - 1}{2\sqrt{3}\frac{\sqrt{3}}{2} + 3}\\ & = \frac{0}{6}\\ & = 0 \end{align} $$

But according to WolframAlpha this is incorrect, and the limit should be 1. What have I done wrong?

Also, as I have only just begun I am unfamiliar with L'Hopital's rule.

share|improve this question
    
Why do you change a sign from the first to the second line? –  egreg Jul 12 at 21:59
    
Mistake, thanks for catching that. –  user3002473 Jul 12 at 21:59
    
The error is still there. –  egreg Jul 12 at 22:06
    
Are you saying $(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3) \neq (2\sin{x} - 1)(2\sqrt{3}\cos{x} - 3)$? I simply flipped the signs from line 1 to line 2 allowing me to cancel out (2\sqrt{3}\cos{x} - 3). –  user3002473 Jul 12 at 22:08
    
Yes, that's exactly what he's saying. –  Code-Guru Jul 12 at 22:08

6 Answers 6

up vote 3 down vote accepted

Hint: $(2\sqrt{3}\cos{x} - 3)(2\sqrt{3}\cos{x} + 3)=12\cos^2x-9=3-12\sin^2x$

Now, do you see a way you can use difference of squares to simplify the following expression?$$\lim_{x\to\pi/6}\frac{(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3)}{3-12\sin^2x}$$

share|improve this answer
    
Oh my gosh I looked at my paper here and I made around 4 or 5 mind-bogglingly dumb mistakes (like saying $(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3) = (2\sin{x} - 1)(2\sqrt{3}\cos{x} - 3)$ along with a few others). Thank you for the help but it turns out my confusion was simply due to lack of attention. –  user3002473 Jul 12 at 22:14

You can solve it like this:

$\lim_{x\to\pi/6}\frac{1 - 2\sin{x}}{2\sqrt{3}\cos{x} - 3}=\frac{2}{2\sqrt{3}} \cdot\lim_{x\to\pi/6}\frac{\frac{1}{2} - \sin{x}}{\cos{x} - \frac{3}{2\sqrt{3}}}=\frac{2}{2\sqrt{3}} \cdot\lim_{x\to\pi/6}\frac{\sin{30^o} - \sin{x}}{\cos{x} - \cos{30^o}}=A$.

Now you can use sum to product trig rules:

$A=\frac{2}{2\sqrt{3}} \cdot\lim_{x\to\pi/6}\frac{2\sin{\frac{30^o-x}{2}}\cos{\frac{{30^0+x}}{2}}}{2\sin{\frac{30^o-x}{2}}\sin{\frac{{30^0+x}}{2}}}=1$ $\blacksquare$

share|improve this answer
1  
I really like the usage of mathworld.wolfram.com/ProsthaphaeresisFormulas.html (+1) –  lab bhattacharjee Jul 13 at 6:09

$$ \begin{align} \lim_{x\to\pi/6}\frac{(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3)}{(2\sqrt{3}\cos{x} - 3)(2\sqrt{3}\cos{x} + 3)} \end{align} $$

You need to multiply out the denominator (and possibly the numerator):

$$ \begin{align} \lim_{x\to\pi/6}\frac{(1 - 2\sin{x})(2\sqrt{3}\cos{x} + 3)}{12\cos^2{x} - 9} \end{align} $$

share|improve this answer

As $\displaystyle\sin x-\sin a=\frac{\sin^2x-\sin^2a}{\sin x+\sin a}$

using Prove $ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $, $\displaystyle \sin x-\sin a=\frac{\sin(x+a)\sin(x-a)}{\sin x+\sin a}$

Similarly, $\displaystyle\cos x-\cos a=\frac{\cos^2x-\cos^2a}{\cos x+\cos a}=\frac{1-\sin^2x-(1-\sin^2a)}{\cos x+\cos a}=-\frac{\sin(x+a)\sin(x-a)}{\cos x+\cos a}$

$$\implies\lim_{x\to a}\frac{\sin a-\sin x}{\cos x-\cos a}=\cdots=\lim_{x\to a}\frac{\cos x+\cos a}{\sin x+\sin a}=\cdots$$

Here $\displaystyle a=\frac\pi6$

This method can be safely employed

in How to evaluate this trigonometric limit?

and in Find the limit as $x$ tends towards $\frac{\pi}{4}$

share|improve this answer
    
@user3002473, How about this? –  lab bhattacharjee Jul 14 at 16:56

$$\lim_{x\to\pi/6}\frac{1 - 2\sin{x}}{2\sqrt{3}\cos{x} - 3}$$

$$=-\frac2{2\sqrt3}\lim_{x\to\pi/6}\frac{\sin x-\sin\frac\pi6}{\cos x-\cos\frac\pi6}$$

$$=-\frac2{2\sqrt3}\lim_{x\to\pi/6}\frac{\sin x-\sin\frac\pi6}{x-\frac\pi6}\cdot\frac1{\lim_{x\to\pi/6}\dfrac{\cos x-\cos\frac\pi6}{x-\frac\pi6}}$$

$$=-\frac2{2\sqrt3}\frac{\dfrac{d(\sin x)}{dx}_{(\text{ at } x=\frac\pi6)}}{\dfrac{d(\cos x)}{dx}_{(\text{ at } x=\frac\pi6)}}$$

$$=\cdots$$

share|improve this answer

Another way is to use change of variables. Let $y = x - \pi/6$. $$ \lim_{x\to\pi/6}\frac{1 - 2\sin{x}}{2\sqrt{3}\cos{x} - 3} = \lim_{y \to 0}\frac{1 - 2\sin{(y + \pi/6)}}{2\sqrt{3}\cos{(y+\pi/6)} - 3} = L $$ But, $$ 1 - 2\sin(y + \pi/6) = (1 - \cos y) - \sqrt{3}\sin y $$ and $$ 2\sqrt{3}\cos{(y+\pi/6)} - 3 = 2\sqrt{3}\bigg(\frac{\sqrt{3}}{2}\cos y - \frac{1}{2}\sin y\biggr) - 3 $$ $$ = 3\cos y - \sqrt{3}\sin y - 3 = -3(1 - \cos y) - \sqrt{3}\sin y $$ Thus, $$ L = \lim_{y \to 0}\dfrac{\dfrac{1 - \cos y}{y} - \dfrac{\sqrt{3}\sin y}{y}}{-3\dfrac{1 - \cos y}{y} - \sqrt{3}\dfrac{\sin y}{y}} = 1 $$ I used the fact that $$ \lim_{y \to 0}\frac{1 - \cos y}{y} = 0 \quad \text{and} \quad \lim_{y \to 0}\frac{\sin y}{y} = 1 $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.